If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-9x + -7) = 8x Reorder the terms: 7(-7 + -9x) = 8x (-7 * 7 + -9x * 7) = 8x (-49 + -63x) = 8x Solving -49 + -63x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -49 + -63x + -8x = 8x + -8x Combine like terms: -63x + -8x = -71x -49 + -71x = 8x + -8x Combine like terms: 8x + -8x = 0 -49 + -71x = 0 Add '49' to each side of the equation. -49 + 49 + -71x = 0 + 49 Combine like terms: -49 + 49 = 0 0 + -71x = 0 + 49 -71x = 0 + 49 Combine like terms: 0 + 49 = 49 -71x = 49 Divide each side by '-71'. x = -0.6901408451 Simplifying x = -0.6901408451
| -10(s+1)=28 | | 3(6-4m)=2(9-6m) | | 8h+1=6h+19 | | 3(5-5x)=7(5-5x) | | 3-x^3=3x-4 | | 1x+9=2x-7 | | 2(5g-5)=3(5g-10) | | -6x+53=5 | | 14y-5=7(2y-2) | | -6+53=5 | | -8x+23=103 | | -3x-14x=85 | | 3h=6h+6 | | 3x*30=180 | | (4x-5)(x-2)= | | 4t-3=13+4t | | 4(3s+4)=76 | | 9x-5y=113 | | 0=12x-12 | | -164=-50x+36 | | 25+7a=27-4a | | -8x-11=45 | | 86=10x+26 | | (4r+2g)*(4r-2g)= | | 11+5x=-9 | | -18x-36=-36 | | f(x)=x^2+10x-3 | | x(x+1)-y(y+1)=0 | | 11x-16=-49 | | 2x^2-(2x/2)=12 | | 38=3x+17 | | 3z-(1-2z)=9 |